Detection of tetrodotoxins in juvenile pufferfish Lagocephalus sceleratus (Gmelin, 1789) from the North Aegean Sea (Greece) by an electrochemical magnetic bead-based immunosensing tool. (30th August 2019) - Leonardo, Sandra; Kiparissis, Sotiris; Rambla-Alegre, Maria; Almarza, Sergi; Roque, Ana; Andree, Karl B.; Christidis, Aris; Flores, Cintia; Caixach, Josep; Campbell, Katrina; Elliott, Christopher T.; Aligizaki, Katerina; et al.
Highlights: An electrochemical immunosensing tool for tetrodotoxin (TTX) screening is developed. High TTX levels in L. sceleratus juveniles are reported for the first time. This fish can be mistaken with edible species, posing a threat to public health. TTX-magnetic bead conjugates provide advantages such as lower matrix effects. Such fast, simple and low-cost analytical tools will help to protect fish consumers. Abstract: Two small Lagocephalus sceleratus juveniles were captured in picarel targeting catches from North Aegean Sea (Greece) in the autumn of 2017. An electrochemical immunosensing tool using magnetic beads as immobilisation support was developed and applied to the rapid screening of tetrodotoxins (TTXs), potent neurotoxins that constitute a food safety hazard when present in seafood. This tool revealed the presence of TTXs in both individuals. Results were compared with those provided by mELISA and LC-HRMS, the latter confirming the presence of TTX. Some of the tissues contained TTX contents close to or above 2 mg/kg. L. sceleratus juveniles had been considered as non-toxic and, to our knowledge, this is the first report of high TTX levels in small L. sceleratus individuals. Such specimens can be mistaken with other edible species, posing a threat to consumers. The availability of low-cost and user-friendly tools for TTXs detection will contribute to guarantee seafood safety.